Medical complications in pregnancy : - Craigo, Sabrina D. (McGraw-Hill, 2005)
This book is the perfect for providing expert care for disorders created or affected by pregnancy. Each disorder-focused chapter opens with a high-yield “pathway” summarizing the best course of action as determined by scientific studies